Two new troglobitic Newportia (Newportia) from Brazil (Chilopoda: Scolopendromorpha) - Ázara, Ludson Neves De; Ferreira, Rodrigo Lopes (Zootaxa, 2014)
Newportia (Newportia) spelaea n. sp. and Newportia (N.) potiguar n. sp. are here described from Bahia and Rio Grande do Norte State, respectively. These two species show highly troglomorphic traits, such as elongation of antennae, legs, ultimate legs, tergites, pronounced depigmentation and reduced sclerotization of the cuticle. Both species occur in caves located in a semi-arid biome (Caatinga) and can be considered troglobites.